(untitled) (R&D Journal, 2018)
Store release from a parent aircraft in the transonic regime is a complex transient interaction to simulate, due to both compressibility effects and the strong interference flow field generated between the parent and store bodies. This work presents the results from a time-accurate transonic numerical simulation of a generic store release case, with detailed attention to ejector force profiles. Confidence limits for time-accurate trajectory calculations with STAR-CCM+® have been improved for this standard benchmark case.